2021
DOI: 10.1101/2021.03.14.435324
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered effective connectivity in sensorimotor cortices: a novel signature of severity and clinical course in depression

Abstract: Functional neuroimaging research on depression has traditionally targeted neural networks associated with the psychological aspects of depression. In this study, in stead, we focus on alterations of sensorimotor function in depression. We used resting-state functional MRI data and Dynamic Causal Modeling (DCM) to assess the hypothesis that depression is associated with aberrant effective connectivity within and between key regions in the sensorimotor hierarchy. Using hierarchical modeling of between-subject ef… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 116 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…Therefore, characterizing neural correlates of the altered sensorimotor functions is important for a comprehensive and translatable understanding of the MDD. In a recent study, Ray and colleagues showed that altered effective connectivity in sensorimotor regions might act as a promising and quanti able candidate marker of depression severity and treatment response (Ray et al, 2021). Here our nding implies that network dysfunction of sensorimotor components occurs in adolescent MDD as well.…”
Section: Alternations In Nodal Centralities In the Ctnsmentioning
confidence: 55%
“…Therefore, characterizing neural correlates of the altered sensorimotor functions is important for a comprehensive and translatable understanding of the MDD. In a recent study, Ray and colleagues showed that altered effective connectivity in sensorimotor regions might act as a promising and quanti able candidate marker of depression severity and treatment response (Ray et al, 2021). Here our nding implies that network dysfunction of sensorimotor components occurs in adolescent MDD as well.…”
Section: Alternations In Nodal Centralities In the Ctnsmentioning
confidence: 55%
“…It is well established that depression and anxiety are highly comorbid. Furthermore, a recent study by Ray et al [43] demonstrated depression associated changes in effective connectivity in sensory and motor cortices. The sadness survey in the NIH toolbox is a self-report measure which assesses sadness using a Computer-Adaptive Test (CAT).…”
Section: Methodsmentioning
confidence: 99%